Temporal Changes of Water Quality Parameters in Rupa Lake and their Impact on Productivity - Husen, Md. Akbal; Dhakal, Ram P; Nepal, Agni P (ZOO-Journal, 2019)
Knowledge on nutrient dynamics of the lake provide basis for modality and extent of exploitation of fishery resources. Therefore, a long-term data of physico-chemical parameters was analyzed for the assessment of changing aquatic environment and its impact on aquatic biodiversity. The physical and chemical properties of water have been changed over 14 years (1994 to 2007). Increase in mean annual concentrations of dissolved oxygen in recent years (2002 to 2007) were recorded in the lake, which indicate improvement in water quality due to lake restoration. Annual mean pH levels were not consistent to produce specific trends. The pH of the water increased from 1994 to 2002, and then decreased continuously in later period. Water transparency increased with the decreased chlorophyll 'a' concentration during 1999 to 2002 due to degraded condition. The higher concentrations (0.010- 0.017 mgl-1) of soluble reactive phosphorous (SRP- PO4) were recorded during 1994 to 2000, later SRP concentration (0.003-0.012 mgl-1) tend to reduce. Effect of fluctuation in the physico-chemical properties on the lake productivity in terms of fish yield was assessed.